2013
DOI: 10.14202/vetworld.2013.879-883
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different drinking water sources in Sokoto North-West Nigeria on performance, carcass traits and haematology of broiler chickens

Abstract: Aim:The study examined the effect of different drinking water sources on performance, carcass characteristics and haematology of broiler chickens.Materials and Methods: 63 unsexed day-old broiler chicks were randomly grouped into three treatment groups (Treatments 1, 2 and 3), each consisting of three replicates of seven chicks each. Treatments 1, 2 and 3 were given water from various sources: pipe borne water; borehole water and well water, respectively from day-old to seven weeks of age. The water samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
4
7
0
Order By: Relevance
“…The performance parameters (BWT, BWG, FI, WI, WI/FI ratio, and FCR) per week showed no significant difference (p>0.05) among the experimental treatments of broiler chickens supplied with different water sources (Tables- 3 and 4 ). The current result is consistent with several previous studies [ 6 - 9 ].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The performance parameters (BWT, BWG, FI, WI, WI/FI ratio, and FCR) per week showed no significant difference (p>0.05) among the experimental treatments of broiler chickens supplied with different water sources (Tables- 3 and 4 ). The current result is consistent with several previous studies [ 6 - 9 ].…”
Section: Resultssupporting
confidence: 94%
“…Studying the carcass responses in this experiment ( Table-6 and 7 ) revealed that, there was no significant difference (p>0.05) in the relative weights (as a percent of final BWT) of eviscerated carcass and internal organs (liver, spleen and heart), for exception bursa and gizzard among the experimental treatments. The results that are in full agreement with authors [ 7 - 9 ], who reported that the different water sources had no significant effect on carcass characteristics. Birds at (T3) showed the higher eviscerated carcass percentage compared with the other experimental treatments.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…well, pipeborne),improper cleaning and maintenance of drinkers or rearing place, feeds, drugs, faeces ,farmers awareness or education are among the factors that triggers water contamination. Therefore, farmers should be made aware ,and innovative systems of water treatment should be applied, proper cleaning of drinkers and cages or farms are mostly needed in order to safeguard poultry production and public health ( Cunningham,1982;Amaral ,2005;Uwaezuoke and Ogbulie, 2008;Aliyu et al .,2013;Dhaka et al .,2013;Ibitoye et al ., 2013;Elsaidy et al, 2015;Sarkingobir and Sarkingobir, 2017;Sarkingobir et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…E .coli reduces weight of poultry (Elsaidy et al, 2015). E. coli in poultry water was determined by past studies such as Ibitoye et al, (2013) from Sokoto. Aliyu et al, (2012) determined it in diverse poultry feeds in Sokoto.…”
Section: Methodsmentioning
confidence: 99%